Bacterial Biohybrid Microswimmers - Bastos-Arrieta, Julio; Revilla-Guarinos, Ainhoa; Uspal, William E.; Simmchen, Juliane (Frontiers in Robotics and AI, 2018)
Over millions of years, Nature has optimized the motion of biological systems at the micro and nanoscales. Motor proteins to motile single cells have managed to overcome Brownian motion and solve several challenges that arise at low Reynolds numbers. In this review, we will briefly describe naturally motile systems and their strategies to move, starting with a general introduction that surveys a broad range of developments, followed by an overview about the physical laws and parameters that govern and limit motion at the micro scale. We characterize some of the classes of biological microswimmers that have arisen in the course of evolution, as well as the hybrid structures that have been constructed based on these, ranging from Montemagno’s ATPase motor to the SpermBot. Thereafter, we maintain our focus on bacteria and their biohybrids. We introduce the inherent properties of bacteria as a natural microswimmer and explain the different principles bacteria use for their motion. We then elucidate different strategies that have been employed for the coupling of a variety of artificial micro-objects to the bacterial surface, and evaluate the different effects the coupled objects have on the motion of the “biohybrid”. Concluding, we give a short overview and a realistic evaluation of proposed applications in the field.